Clinical Profile of Cirrhotic Patient with Esophageal Varices Who Undergone Band Ligation in Cipto Mangunkusumo Hospital - Kemal Fariz Kalista; Cosmas Rinaldi Adithya Lesmana; Andri Sanityoso Sulaiman; Rino Alvani Gani; Irsan Hasan (Jurnal Penyakit Dalam Indonesia)
Introduction. Liver cirrhosis (LC) is the end stage of chronic liver disease. One of the main complication caused by LC is esophageal varices (EV). Bleeding due to EV rupture is the main cause of mortality in patient with LC. EV band ligation can be used for primary or secondary prophylaxis to prevent bleeding. The purpose of this study was to know the clinical profile of LC patient with EV who underwent band ligation and who not underwent band ligation.